Security management of BYOD and cloud environment in Saudi Arabia - Khalid Almarhabi; Adel Bahaddad; Ahmed Mohammed Alghamdi (Alexandria Engineering Journal, 2023)
The increasing trend of Bring Your Own Device (BYOD) to work has led to a significant surge in the risks related to network security. This trend is very beneficial to employers and employees alike in any organisation. The wide infiltration of spyware, malware and similarly suspicious downloads into personal devices has forced the government to reconsider its policies regarding data security. The malicious programs get downloaded onto the personal devices without the user even realising. This could disastrously affect the individuals and the governments. In the case of such an event, the BYODs become risky as they can make unauthorised policy changes and leak sensitive data into the public domain. This type of privacy breach leads to a domino effect with major legal and financial implications, and a decreased productivity for the organisations and governments. This presents a huge challenge as the governments have to consider the user rights and privacy laws and also protect the networks from these attacks. In this study, the researchers have proposed a novel technical framework that could assist the Saudi government. This framework was designed after determining the challenges that were faced by the government, based on the citizen perspectives, to control all risks challenging the use of the BYODs. This framework decreased the number of system restrictions and enforced access control policies for BYODs and cloud environments. The preliminary results of this study were positive and indicated that the framework could decrease the problems related to access control.